2015
DOI: 10.1111/eea.12273
|View full text |Cite
|
Sign up to set email alerts
|

Using multiple traits to estimate the effects of heat shock on the fitness of Aphidius colemani

Abstract: Extreme temperature events are a great challenge for most ectotherms, particularly for the immature stages of parasitoids, as they do not possess the ability to behaviourally thermoregulate. In this study, we measured the effect of an acute heat shock, combined with desiccation stress (34 °C and 35% r.h. during 10 h) during the mummy stage on several fitness‐related traits of emerging adults of the aphid parasitoid Aphidius colemani Viereck (Hymenoptera: Braconidae: Aphidiinae). Our results showed that the eme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 61 publications
2
13
0
Order By: Relevance
“…This is because they are affected both directly and indirectly through the effects of high temperature on the insect host and the host plant (Agosta et al., 2018; Hance et al., 2007; van Baaren et al., 2010). Previous studies have shown that TE may deleteriously affect the behavior and performance of parasitoids in terms of survival, development, flight and host‐finding efficiency, and oviposition behavior (Agosta et al., 2018; Chen, Gols, et al., 2019; Flores‐Mejia et al., 2016; Jerbi‐Elayed et al., 2015). TE exposure has also been shown to affect predator–prey interactions by modifying consumption rate, growth, and behavior, potentially leading to differences in voltinism and phenology, predator population size, and dispersal (Damien & Tougeron, 2019; Jamieson et al., 2012; Sentis et al., 2017).…”
Section: Effects Of Te On Trophic Interactionsmentioning
confidence: 99%
“…This is because they are affected both directly and indirectly through the effects of high temperature on the insect host and the host plant (Agosta et al., 2018; Hance et al., 2007; van Baaren et al., 2010). Previous studies have shown that TE may deleteriously affect the behavior and performance of parasitoids in terms of survival, development, flight and host‐finding efficiency, and oviposition behavior (Agosta et al., 2018; Chen, Gols, et al., 2019; Flores‐Mejia et al., 2016; Jerbi‐Elayed et al., 2015). TE exposure has also been shown to affect predator–prey interactions by modifying consumption rate, growth, and behavior, potentially leading to differences in voltinism and phenology, predator population size, and dispersal (Damien & Tougeron, 2019; Jamieson et al., 2012; Sentis et al., 2017).…”
Section: Effects Of Te On Trophic Interactionsmentioning
confidence: 99%
“…Temperature is a dominant abiotic factor that strongly affects organisms’ behaviour, physiology, life history, distribution, and abundance 14 . Insects have an optimal temperature range to which their biological functions are best adapted; under supra-optimal temperatures, insects might incur physiological costs and suffer damage that lowers their performance 15 . Most insects have the ability to tolerate some degree of temperature fluctuation 16 , but lethal temperatures are usually between 40 and 50 °C depending on insect species and life stage 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Temperature is one of the most important environmental factors affecting life history, behavioral and physiological traits, population structure, and community composition in insects ( Zhang et al, 2015b ; Esperk et al, 2016 ). Insects have an optimal temperature range to which their biological functions are best adapted; over this range, insects might suffer physiological costs and fitness decrease ( Jerbi-Elayed et al, 2015 ). Climate change has led to an increase in the frequency, intensity, and length of extreme high temperatures around the globe and this trend is expected to continue ( Ma et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%